2022
DOI: 10.56772/jkk.v13i2.261
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penggunaan Kontrasepsi Suntik Terhadap Peningkatan Tekanan Darah

Abstract: Akseptor keluarga berencana yang menggunakan kontrasepsi hormonal (pil dan suntik) dalam kurun waktu tertentu sering mengeluhkan masalah kesehatan, salah satunya adalah hipertensi atau tekanan darah tinggi. Tujuan: Mengetahui hubungan penggunaan kontrasepsi suntik terhadap peningkatan tekanan darah. Penelitian analitik dengan pendekatan Cross Sectional. Sampel dalam penelitian ini adalah akseptor KB suntik yang dijumpai saat dilakukan penelitian di Bidan Asih Ngemplak Boyolali pada bulan Januari-Maret 2022 seb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…This is in line with research conducted by (Norlita et al, 2018) which showed that there was no significant relationship between the use of injectable contraceptives and blood pressure in injecting family planning acceptors at the Harapan Raya Health Center in Pekanbaru. In the study (Setyorini et al, 2022) also showed the use of injectable contraception was not associated with an increase in blood pressure.…”
Section: Hormonal Contraceptionmentioning
confidence: 78%
“…This is in line with research conducted by (Norlita et al, 2018) which showed that there was no significant relationship between the use of injectable contraceptives and blood pressure in injecting family planning acceptors at the Harapan Raya Health Center in Pekanbaru. In the study (Setyorini et al, 2022) also showed the use of injectable contraception was not associated with an increase in blood pressure.…”
Section: Hormonal Contraceptionmentioning
confidence: 78%
“…In the use of hormonal contraception, the majority of respondents used hormonal contraception (89.2%) with the most use of the type of contraception, namely injection (56.7%). Hormonal birth control is a contraceptive method that contains only the hormone estrogen, only progesterone or a combination of both, apart from being useful in preventing pregnancy in couples of childbearing age, the use of hormonal contraception can cause several side effects for its users, one of which is hypertension (Setyorini et al, 2022). Hormonal contraception contributes to increasing blood pressure by 10% higher than women who do not use hormonal contraception.…”
Section: Discussionmentioning
confidence: 99%
“…3 Suplemen gizi yang diberikan menurut Peraturan Menteri Kesehatan Nomor 51 tahun 2016 tentang Standar Produk Suplementasi Gizi, meliputi kapsul vitamin A, tablet tambah darah (TTD), makanan tambahan untuk ibu hamil, vitamin dan mineral. 4 Kurang Energi Kronis (KEK) merupakan keadaan dimana ibu menderita kekurangan asupan energi dan protein yang berlangsung menahun (kronis) yang mengakibatkan timbulnya gangguan kesehatan pada ibu sehingga kebutuhan ibu hamil akan zat gizi yang semakin meningkat tidak terpenuhi. Ibu hamil Kurang Energi Kronik (KEK) menjadi salah satu faktor determinan terjadinya risiko gangguan masalah gizi dan kesehatan pada bayi yang dilahirkan.…”
Section: Oajjhsunclassified